An analysis of the Scharfetter-Gummel box method for the stationary semiconductor device equations - Miller, J.J.H.; Wang, Song (EDP SCIENCES S A, 1994)
An exponentially fitted box method, known as the Scharfetter-Gummel box method, for the semiconductor device équations in the Slotboom variables is analysed. The method is formulated as a Petrov-Galerkin finite element method with piecewise exponential basis functions on a triangular Delaunay mesh. No restriction is imposed on the angles in the triangulation, The stability of the method is proved and an error estimate for the Slotboom variables in a discrete energy norm is given. When restricted to the two continuity équations the error estimate dépends only on the first-order seminorm of the exact flux and the approximation error ofthe zero order and inhomogeneous terms. This is in contrast to standard error estimâtes which depend on the second order seminorm of the exact solution. The évaluation of the ohmic contact currents is discussed and it is shown that the approximate ohmic contact currents are convergent and conservative.